A Game Theoretic Analysis of Cooperation and Conflict in the India-China LAC Dispute - Mene, Swati; Soni , Manjula; Singh , M.M. (International Journal of Membrane Science and Technology, 2023)
This paper examines the ongoing dispute at the Line of Actual Control (LAC) between India and China through the lens of the Prisoner's Dilemma with a twist: Pakistan's involvement. We analyze the strategic options for India and China, considering the potential benefits and drawbacks of cooperation or defection, with two scenarios: Pakistan supporting China and Pakistan remaining neutral.